Analysis of Factors Influencing Shopee E-Commerce Purchase Decisions - Aden Tegar Kurniawan; Farida Indriani (PT. Publikasiku Academic Solution, 2023)
This study aims to analyze the factors that drive consumers to choose Shopee as a marketplace compared to other applications. The timeframe for this research was conducted from 2022-2023 with employees of PT. Telkom Semarang as an object. The sampling method used is non-probability sampling and accidental sampling, namely determining the sample based on natural or reflex factors. The final sample numbered 100 employees. Quantitative analysis using the structural equation modeling (SEM)-partial least squares path (PLS) method is used to test the data because it involves intervening variables. The results show that convenience has no effect on purchasing decisions, but convenience can influence trust. Meanwhile, trust is not able to be a good intervention between convenience and purchasing decisions. perceived risk has no effect on purchasing decisions, and perceived risk also has no effect on trust. Meanwhile, trust is not able to be a good intervention between perceived risk in purchasing decisions. Impulsive buying has no effect on purchasing decisions. However, impulsive buying affects trust. Meanwhile, trust can be a good intervention between impulsive buying and buying decisions. trust has a positive effect on buying decisions.